The effect of clopidogrel on pharmacokinetics of ivabradine and its metabolite in rats. (September 2015) - Sun, Wei; Wang, Zhe; Chen, Hui; Zhang, Xiao-Dan; Huang, Cheng-Ke; Lian, Qing-Quan; Shang-Guan, Wang-Ning; Zhu, Guang-Hui; Hu, Guo-Xin; Wang, Zeng-Shou
Abstract The present study aimed to investigate the effect of clopidogrel (CLO) on pharmacokinetics of ivabradine (IVA) and its metabolite in rats and develop a reliable method to determine IVA and its metabolite N-demethyl ivabradine in serum. Healthy male SD rats were randomized to be given 0.8 mg/kg IVA or IVA combined with 8 mg/kg CLO. Blood samples were collected at 0.083, 0.16, 0.25, 0.5, 1, 1.5, 2, 3, 4, 6, 8, 12, 24 h after administration. The serum concentrations of IVA and N-demethyl ivabradine were determined by ultra-performance liquid chromatography–mass spectrometry and pharmacokinetic parameters were calculated using DASver3.0 software. The parameters of AUC(0 − t), AUC(0 − ∞), and Cmax for IVA in the group of IVA + CLO were significantly higher than those in the group of IVA (p < 0.01); the half-time (t1/2) in the IVA + CLO group was extended compared to IVA (p < 0.01) and CL/F was dropped obviously (p < 0.01). The decreases in AUC(0 − t), AUC(0 − ∞), and Cmax for N-demethyl ivabradine in the group of IVA + CLO was significantly compared to the group of IVA (p < 0.01). CL/F was higher than IVA (p < 0.01) and the t1/2 was slightly increased. In this study, we find that CLO restrains the metabolism of IVA into N-demethyl ivabradine, which may be related to its competitive inhibition effect on cytochrome P450 isoform 3A4(CYP3A4).